Intensity‐modulated radiotherapy followed by a brachytherapy boost for oropharyngeal cancer. Issue 12 (9th March 2013) - Al‐Mamgani, Abrahim; Levendag, Peter C.; van, Peter; Meeuwis, Cees A.; Sewnaik, Aniel; Teguh, David N.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to reduce the incidence of radiation‐induced toxicity in patients with early‐stage oropharyngeal cancer, using highly conformal radiation techniques. Methods Between 2000 and 2011, 167 patients with T1‐3N0‐3 oropharyngeal cancer were treated with 46‐Gy intensity‐modulated radiation therapy (IMRT) followed by 22‐Gy brachytherapy boost. In patients with node‐positive disease, neck dissection was performed. Results The 5‐year Kaplan–Meier estimates of local control, regional control, disease‐free survival (DFS), and overall survival (OS) were 94%, 97%, 84%, and 72%, respectively. Feeding tubes were required in 26% of the patients. Grade ≥2 late xerostomia and dysphagia were 11% and 8%, respectively. Chemotherapy, tumor subsite, and bilateral neck irradiation correlate significantly with toxicity. Quality of life (QOL) scores deteriorate during and shortly after treatment but returned in all scales to baseline scores within 6 to 12 months, with the exception of xerostomia. Conclusion Brachytherapy boost and neck dissection (in node‐positive oropharyngeal cancer) after 46‐Gy of IMRT resulted in excellent outcomes with low incidence of late toxicity and good QOL scores. © 2013 Wiley Periodicals, Inc. Head Neck 35: 1689–1697, 2012